2004
DOI: 10.1094/mpmi.2004.17.10.1114
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Population Genetic Analysis Differentiates Two Virulence Mechanisms of the Fungal Avirulence Gene NIP1

Abstract: Deletion or alteration of an avirulence gene are two mechanisms that allow pathogens to escape recognition mediated by the corresponding resistance gene in the host. We studied these two mechanisms for the NIP1 avirulence gene in field populations of the fungal barley pathogen Rhynchosporium secalis. The product of the avirulence gene, NIP1, causes leaf necrosis and elicits a defense response on plants with the Rrs1 resistance gene. A high NIP1 deletion frequency (45%) was found among 614 isolates from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
114
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 49 publications
6
114
3
Order By: Relevance
“…A common evolutionary strategy for evading recognition is the loss of an entire avirulence gene (Schürch et al ., 2004; Mackey & McFall, 2006; de Jonge et al ., 2012; Hartmann et al ., 2017). However, loss of Avr3D1 was not observed in any of the 132 global strains, despite its location in a highly plastic genomic region, as shown by presence/absence polymorphisms for neighbouring genes and transposable elements.…”
Section: Discussionmentioning
confidence: 99%
“…A common evolutionary strategy for evading recognition is the loss of an entire avirulence gene (Schürch et al ., 2004; Mackey & McFall, 2006; de Jonge et al ., 2012; Hartmann et al ., 2017). However, loss of Avr3D1 was not observed in any of the 132 global strains, despite its location in a highly plastic genomic region, as shown by presence/absence polymorphisms for neighbouring genes and transposable elements.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, only a few cases are reported in the literature where fungal isolates were shown to break the Rrs2 mediated resistance of cultivar Atlas in Europe. The study of Schürch et al (2004) showed that two isolates (AU2 and RS88CA27) out of 41 tested were able to break the resistance. Lehnackers and Knogge (1990) identified four races which were able to complete the developmental cycle from spore germination to sporulation on Atlas.…”
Section: Fungal Strains Lacking the Nip1 Gene Or Strains With Specifimentioning
confidence: 99%
“…Of the remaining 16 variants, four have been studied in more detail. NIP1 types I and II, which were found in .50% of all NIP1-carrying fungal isolates (Schü rch et al, 2004), are elicitor active on Rrs1 barley, with type II showing somewhat lower activity than type I. In contrast, types III and IV are drastically less active or inactive (Rohe et al, 1995;Fiegen and Knogge, 2002).…”
mentioning
confidence: 99%
“…secalis strains virulent on Rrs1 barley plants either lack the NIP1 gene or carry point mutations in the coding sequence that result in single amino acid alterations, which strongly reduce or abolish the biological activity of the gene product (Rohe et al, 1995). Comparison of the deduced amino acid sequences encoded by NIP1 alleles from more than 200 fungal isolates so far led to the classification of 18 NIP1 variants (Rohe et al, 1995;Schü rch et al, 2004), two of which may not be expressed properly due to mutations in the start codon and in the acceptor splice site, respectively. Of the remaining 16 variants, four have been studied in more detail.…”
mentioning
confidence: 99%